2013
DOI: 10.1007/s10570-013-9952-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microcrystal cellulose and cellulose whisker on biocompatibility of cellulose-based electrospun scaffolds

Abstract: To investigate the potential application of microcrystal cellulose (MCC) and cellulose whisker (CW) in the electrospun vascular tissue scaffolds, cellulose acetate (CA) and cellulose composite scaffolds containing MCC and CW were electrospun from CA solutions and deacetylation. Structure and morphology of MCC, CW and the fibrous composite scaffolds were investigated using FT-IR, SEM, TEM and AFM. The wettability of the scaffolds was evaluated by water contact angle analysis. The effect of MCC and CW on the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…The potential application of microcrystalline cellulose and CNCs as fillers in electrospun CA for vascular tissue scaffolds has been investigated 171 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 direction, having a positive effect on creating a more uniform morphology (diameters ranging from 212 nm to 221 nm). This ordered microstructure combined with the strong interfacial bonding between CNCs and the regenerated cellulose matrix, remarkably improved the tensile properties of non-woven mats (tensile strength and elastic modulus increased by 101.7 % and 171.6 %, respectively, in the fiber alignment direction, with 20 % loading of CNCs).…”
Section: Nano and Microfibers Matsmentioning
confidence: 99%
“…The potential application of microcrystalline cellulose and CNCs as fillers in electrospun CA for vascular tissue scaffolds has been investigated 171 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 direction, having a positive effect on creating a more uniform morphology (diameters ranging from 212 nm to 221 nm). This ordered microstructure combined with the strong interfacial bonding between CNCs and the regenerated cellulose matrix, remarkably improved the tensile properties of non-woven mats (tensile strength and elastic modulus increased by 101.7 % and 171.6 %, respectively, in the fiber alignment direction, with 20 % loading of CNCs).…”
Section: Nano and Microfibers Matsmentioning
confidence: 99%
“…Jia et al 81 reported potential application of microcrystal cellulose (MCC) and CNC as a ller of electrospun cellulose acetate vascular tissue scaffolds to improve biocompatibility. Thus, although the present work should be biocompatible, given that both components have been previously tested separately, future investigations are needed to characterize the toxicology of these cellulose nanocomposites materials thorough in vitro and in vivo testing, to conrm the potential biomedical application.…”
Section: -79mentioning
confidence: 99%
“…CNFs have been investigated as a promising substrate for regenerative medicine and wound healing such as scaffolds for tissue-engineered meniscus, blood vessels, and ligament or tendon substitutes (Mathew et al 2011(Mathew et al , 2012Jia et al 2013;Mathew et al 2013;Lin and Dufresne 2014). The applicability of CNFs as hemodialysis membranes (Ferraz et al 2012(Ferraz et al , 2013, antimicrobial nanomaterials (Martins et al 2012;Liu et al 2014) and in the pharmaceutical industry as films for long-lasting sustained drug delivery (Valo et al 2011;Kolakovic et al 2012) has also been documented.…”
Section: Introductionmentioning
confidence: 99%